Dissecting mammalian immunity through mutation - Siggs, O (Nature Publishing Group, 2014)
Although mutation and natural selection have given rise to our immune system, a well-placed mutation can also cripple it, and within an expanding population we are recognizing more and more cases of single-gene mutations that compromise immunity. These mutations are an ideal tool for understanding human immunology, and there are more ways than ever to measure their physiological effects. There are also more ways to create mutations in the laboratory, and to use these resources to systematically define the function of every gene in our genome. This review focuses on the discovery and creation of mutations in the context of mammalian immunity, with an emphasis on the use of genome-wide chemical and CRISPR/Cas9 mutagenesis to reveal gene function. © 2014 Australasian Society for Immunology Inc.